The Challenges of ST-Elevation Myocardial Infarction in COVID-19 Patients - Ju Young Bae; Khalil Ian Hussein; Christopher John Howes; John Francis Setaro (Case Reports in Cardiology)
By July 2021, the United States had over 34.4 million confirmed COVID-19 cases. Various cardiovascular manifestations of COVID-19 have been reported including ST-elevation myocardial infarction (STEMI), and there is concern that SARS-CoV-2 may be associated with a higher thrombus burden. We performed a retrospective chart review of 535 adult patients with COVID-19 admitted at Yale-New Haven Health Greenwich Hospital from February 1, 2020, to May 13, 2020. All admitted patients had undergone testing for serum troponin I and various inflammatory markers, and we identified three patients who were diagnosed with acute STEMI. Data was collected via manual chart review and included patient demographics, comorbidities, laboratory tests, electrocardiogram (ECG) results, echocardiography results, diagnoses during hospitalization, inpatient therapies, and outcomes including length of hospital stay, revascularization results, and mortality. Three of our patients had obstructive coronary artery disease confirmed via angiography. One subject was noted to display vasospasm in addition to coronary atherosclerotic obstruction and refractory thrombus formation. Among our patients with COVID-19 and STEMI, presentations were variable in terms of timing of onset of ECG changes, age, gender, race, comorbidities, symptomology, and outcomes.